2018
DOI: 10.1111/nbu.12337
|View full text |Cite
|
Sign up to set email alerts
|

Working hours and cardiometabolic health – an emerging area of nutritional research

Abstract: Multifactorial work‐related diseases are diseases that occur in the general population, but may be exacerbated or partially caused by occupational exposures. There is increasing evidence to suggest that type 2 diabetes and cardiovascular diseases are associated with duration and time of working hours. Despite the role of diet in the aetiology of cardiometabolic disease being well established, gaps remain in understanding the relationship between working hours and diet. Studies that have compared the diets of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Chrono‐nutrition includes research into the distribution of energy intake, meal frequency and regularity, the duration of eating and fasting periods, and the relative importance of these factors for metabolic health and chronic disease risk (Flanagan et al, 2020; Pot et al, 2016). This Virtual Issue brings together papers recently published in Nutrition Bulletin discussing different aspects of chrono‐nutrition, including sleep, breakfast consumption and time‐restricted feeding (Figure 1) (Clayton et al, 2020; Darzi et al, 2017; Edinburgh et al, 2017; Gibson, 2018; Gibson‐Moore & Chambers, 2019; Lynch et al, 2021; Ruddick‐Collins et al, 2018). Other elements of chrono‐nutrition such as meal regularity, meal frequency and clock time (time of eating) are beyond the scope of this Virtual Issue.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chrono‐nutrition includes research into the distribution of energy intake, meal frequency and regularity, the duration of eating and fasting periods, and the relative importance of these factors for metabolic health and chronic disease risk (Flanagan et al, 2020; Pot et al, 2016). This Virtual Issue brings together papers recently published in Nutrition Bulletin discussing different aspects of chrono‐nutrition, including sleep, breakfast consumption and time‐restricted feeding (Figure 1) (Clayton et al, 2020; Darzi et al, 2017; Edinburgh et al, 2017; Gibson, 2018; Gibson‐Moore & Chambers, 2019; Lynch et al, 2021; Ruddick‐Collins et al, 2018). Other elements of chrono‐nutrition such as meal regularity, meal frequency and clock time (time of eating) are beyond the scope of this Virtual Issue.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that shift workers, especially those working at night, are at an increased risk of developing chronic non‐communicable diseases such as type 2 diabetes and cardiometabolic diseases (Depner et al, 2014; Reutrakul & Knutson, 2015). Despite the known role of diet in the aetiology of cardiometabolic disease, gaps remain in understanding the relationship between working hours and diet (Gibson, 2018). Gibson's review in this Virtual Issue summarises the current research and future directions in the field of working hours and nutrition research (Gibson, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations